Implementation of Cooperative Learning Model Type TAI (Team Assisted Individualization) to the Clothing Sewing Element of a Stand Collar in Class XI SMKN 3 Probolinggo - Dyantina, Nahilla; Hidayati, Lutfiyah; Nashikhah, Ma’rifatun; Arifiana, Deny (PT. Riset Press International, 2024)
This research aims to determine the effect of implanting the TAI-type cooperative learning model with the following research variables: 1) implementation of learning model syntax, 2) learning results, and 3) student motivation learning. This research was conducted at SMKN 3 Probolinggo. This type of research is quantitative research with pre-experimental one-group pretest and post-test. The data sample in this research is fashion class XI, with 32 students. The data in the study were obtained using several methods: observation, practice test, and questionnaires. The research results show: 1) implementation of learning model syntax is good with a 3,5 score; 2) learning results showed a 37,5%% pass percentage and an average score of 69,8 before, then after that showed an increase with a 90,6% pass percentage and an average score of 80,1; 3) student's motivation learning showed an increase of an average 68,26% to 83,04%.